FAKE NEWS AS THE NEW REALITYOF POWER INDUSTRY OPERATION - Stefaniuk, Tomasz (Management and Administration Journal, 2025)
Access to information and the ability to disseminate the same have today become seamless. On the one hand, the number of available data is snowballing. On the other hand, new threats are emerging, such as fake news items; albeit many of the origins can be traced back to the outbreak of the SARS-CoV-2. A corresponding phenomenon could be noted at the time of the Russian military invasion of Ukraine in 2022. Western sanctions and Russian efforts to blackmail Europe through its energy supply, contributed to a growing number of fake news concerning the energy market. The above trajectories have prompted the author to analyse the phenomenon of fake news as being the new reality that has had a significant impact on the operations of both energy recipients and energy market. The purpose of the article is to determine the extent of false news, above all, those relating to the power industry, and public susceptibility to fake news. The findings of the conducted research demonstrate that fake news about the power industry is a common occurrence; although, the extent of energy-related news is smaller than that of disinformation regarding, say, the COVID-19 pandemic. Nonetheless, whenever disinformation about the energy technology reaches the public, it is likely to be subjected to distortion and misrepresentation.